Math rashes and other classroom tales - Evans, Douglas, 1953-; Di Fiori, Lawrence (Asheville, NC : Front Street, 2000)
This collection of nine short stories presents episodes of education gone awry.
Keywords: Schools -- Juvenile fiction; Children's stories, American; Schools -- Fiction; Short stories